A combined confirmatory factor analysis and fuzzy-analytic hierarchy process-TOPSIS (CFAT) framework for measurement of airline service quality. (2016) - Raut, Rakesh D.; Kamble, Sachin S.; Jha, Manoj Kumar
The purpose of this study is to present an integrated CFA-FAHPTOPSIS (CFAT) framework that uses a confirmatory factor analysis (CFA), fuzzy-analytic hierarchy process (FAHP) and technique for order preference by similarity to ideal solution (TOPSIS) for measuring multi criteria airlines service quality dimensions. The proposed CFAT framework is an integration of CFA, FAHP-TOPSIS. This paper validates the CFAT framework for measuring service quality in the Indian airline industry. For this purpose, we developed six main criteria and 28 sub-criteria based on review of literature. The validations were carried using confirmatory factor analysis and were based on data collected through a sample survey on 300 air passengers from India. Three experts were used to rank the identified criteria across four domestic airlines in India. The final ranking of the airlines were based on FAHP-TOPSIS. The study revealed that cabin service, was the highest ranked service quality dimensions followed by booking service, check in service and responsiveness. Timeliness of flight and special offers and freebies scored low on the ranking.